Shone᾽s complex in pediatric age group: clinical characteristics, structural components, interventions, and outcomes of a cohort from a single center - Shaimaa Rakha; Marwa Said Ali; Ahmad Abd El Aleem El Derie; Yahya Wahba; Mohammed Magdy Abo Elkheir (BMC Pediatrics)
Abstract Background Shone’s complex (SC) comprises multi-level left-sided obstructive cardiac lesions. Limited research has addressed SC in the pediatric age, especially the factors impacting outcomes. Therefore, the current work aimed to study clinical, structural, interventional aspects, and outcomes of SC cohort in childhood. Methods A retrospective analysis of SC cases from a single tertiary center was conducted. Demographics and clinical data were collected. Echocardiographic data, other imaging modalities, and required interventions (surgical or transcatheter) were determined. Outcomes regarding morbidity and mortality were collected. Results Twenty five cases were included;17 (68%) were males with a median age of one month (0.2–4.8) at presentation and 33 (5–60) months at the last follow-up. All patients were diagnosed with incomplete SC, with the commonest lesions: Parachute mitral in 86% and aortic coarctation (COA) in 72%. Cardiac multi-slice CT (MSCT) was indicated in 16 (64%), and transesophageal echocardiography in 2 (8%). No intervention was performed in 5 (20%) cases, while interventional catheterization was performed in 4 (16%) and surgery was performed in 19 (76%). The mortality rate in the cohort was 3 (12%), with age of the patient, weight, and weight Z-score at the last follow-up significantly lower in deceased cases. The proportion of cases with suppressed myocardial contractility at the initial presentation was statistically significant in the deceased group (p = 0.03). However, anthropometrics and demographics at presentation, SC components, and interventions did not differ significantly between the two groups. Conclusion Shone’s complex is primarily presented in the atypical incomplete subtype. In pediatric age, parachute mitral and COA are the most common lesions. Echocardiography with MSCT could achieve a non-invasive, comprehensive diagnosis and guide the required intervention. The family should be informed of potential recurrence, progression, or reintervention for SC lesions, emphasizing the need for prolonged follow-up.